Inside the White House : Stories from the World's Most Famous Residence - Grove, Noel (Washington, D.C. National Geographic, 2013)
In collaboration with the White House Historical Association, National Geographic presents this authoritative overview of America's first home featuring never-before published stories and photographs. Organized by theme, discover what makes the White House tick--from its beginnings to the modern day, from the architecture, to the staff, to the first families. Learn fascinating details of the real-life Downton Abbey staff who run this grand home. Marvel at the elaborate detail that goes into hosting a state dinner. Meet the beloved pets who've inhabited 1600 Pennsylvania Avenue. Read about celebrity visitors, the media, and the security so critical in today's world. Sidebars contain tidbits of rare information, and an appendix includes an illustrated time line of all White House First Families as well as a complete index. Photos include intimate and candid glimpses of life inside the White House--some never before seen, others long forgotten, and most never displayed in such large format.
Includes Colored Illustrations and Index.
Keywords: White House (Washington, D.C.) -- Miscellanea -- Presidents